Neurological and psychiatric manifestations of post Ebola syndrome in Sierra Leone. (23rd February 2017) - Howlett, P; Walder, A; Lisk, D; N'jai, A; Lado, M; Brown, C; Sesay, F R; Semple, M G; Scott, J T
Abstract: Background: Neurological and psychiatric sequelae in survivors of Ebola virus disease have been noted in previous epidemics, but few details have been documented. One case-report reported abnormal CT brain findings in one survivor. We aimed to document full neurological history and clinical examination findings, psychiatric screening, and the need for brain imaging in people who survived Ebola virus disease. Methods: Adults (>16 years) in Sierra Leone who had survived Ebola virus disease with defined criteria of confirmed disease and one major or two minor symptoms were invited to attend clinic. Patients underwent full history, neurological examination, and psychiatric screening. Patients were referred, as necessary, to a tertiary neurology and psychiatric clinic, where brain CT scans were requested. Findings: 87 (25%) of 354 patients in the initial cohort fitted the defined criteria. 38 of 45 patients who were contactable attended our screening clinic (24 women [63%], median age 34 years [IQR 25–43]). Median length of initial stay in hospital during Ebola virus disease was 21 days (13–28) and median time to our screening clinic post discharge was 431 days (402–497). 17 (45%) of the 38 clinic attenders reported loss of consciousness and seven (18%) reported seizures during their acute phase. In the screening clinic, 14 (50%) of 28 patients with headache reported eye symptoms (eye pain, itching, redness, blurred vision, or altered vision), seven (25%) photophobia, six (21%) intermittent fevers, five (18%) dizziness or vertigo, two (7%) tinnitus, and two (7%) scotoma. Headaches were usually intermittent and localised as frontal, unilateral, or band-like. 23 (61%) of the clinic attenders were offered referral to a tertiary neurological and psychiatric clinic, and 17 (42%) required CT brain scanning. At the screening clinic, psychiatric symptoms included insomnia (21/38, 55%), depression (12/38, 32%), and anxiety (11/38, 29%). Interpretation: A broad range of important neurological and psychiatric sequelae were present in our selected group of Ebola virus disease survivors over a year after initial discharge. Intermittent headaches, associated with photophobia, intermittent fever, and dizziness or vertigo, were the most frequent neurological features. Common psychiatric symptoms included insomnia, depression, and anxiety. Our experience suggests that there is a need for tertiary level neurological and psychiatric clinics. Funding: JTS is supported by the Wellcome Trust. MGS is supported by the UK National Institute for Health Research Health Protection Research Unit in Emerging and Zoonotic Infections. This project is supported by the Enhancing Research Activity in Epidemic Situations.